A comparison between micro hollow cathode discharges and atmospheric pressure plasma jets in Ar/O2 gas mixtures. (26th October 2016) - Lazzaroni, C; Chabert, P
Abstract: Using global models, micro hollow cathode discharges (MHCDs) are compared to radiofrequency atmospheric pressure plasma jets (APPJs) in terms of reactive oxygen species (ROS) production. Ar/O2 gas mixtures are investigated, typically with a small percentage of oxygen in argon. The same chemical reaction set, involving 17 species and 128 chemical reactions in the gas phase, is used for both devices, operated in the typical geometries previously published; the APPJ is driven by a radiofrequency voltage across a 1 mm gap, at atmospheric pressure, while the MHCD is driven by a DC voltage source, at 100 Torr and in a 400 μ m hole. The MHCD may be operated either in the self-pulsing or in the normal (stationary) regime, depending on the driving voltage. The comparison shows that in both regimes, the MHCD produces larger amounts of O 2 ∗, while the APPJ produces predominantly reactive oxygen ground state species, O and O 3 . These large differences in ROS composition are mostly due to the higher plasma density produced in the MHCD. The difference in operating pressure is a second order effect.